2013
DOI: 10.1007/s11434-013-5786-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, optoelectronic properties of novel zinc Schiff-base complexes

Abstract: Two novel zinc Schiff-base complexes, bis-(N-(2-hydroxybenzidene)-p-aminodimethylaniline)zinc(II) (2) and bis-(N-(2-hydroxy-1-naphthidene)-p-aminodimethylaniline)zinc(II) (4) were designed and synthesized. Both the complexes exhibit good solubility in organic solvents and excellent thermal stabilities. A single crystal of 2 was grown and its crystalline structure was determined from X-ray diffraction data. Analysis of the electronic structures of both the zinc complexes calculated by density functional theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59]. ; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59]. ; in pharmaceuticals; and as catalyst [53] They are also used in dyes [54], polymers, [54] as well as they are applied in nanotechnology [55], laser [56], transistor [57], in defense as gas generating agents [58], and pyrotechnic mixtures [59].…”
Section: Applicationsmentioning
confidence: 99%
“…Nickel, cobalt, cadmium, and copper complexes with carbohydrazide have been attracted more attention because of its variety of applications in defense. Sonawane et al [57] have reported the copper, nickel, and cobalt carbohydrazide nitrate complexes and studied their burning rate for propellant composition. Such types of compounds are used in Pyrotechnics as they possibly act as flame colorants.…”
Section: Scope Of Schiff Bases and Their Complexes For Nanobiotechnologymentioning
confidence: 99%
“…To endorse the experimental results and to further explore the nature of the optical response of these probes towards anions, both sensors and their deprotonated species were examined theoretically by using DMol 3 package with DFT calculations run through GGA with basis set DNP (double numeric plus polarization) . The optimized structures of (1) , (2) and (3) are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The azomethine bond possesses similar isoelectronic characteristics to vinyl bond, giving rise to similar optoelectronic and thermal properties [20] [21] [22]. However, most of the Schiff base derivatives prepared for OLED applications focused on phosphorescent luminescent materials [23] [24] [25] [26] [27]. To our knowledge, few studies focused on hole-buffering application for optoelectronic devices [15].…”
Section: Introductionmentioning
confidence: 99%